Oxford urdu ka guldasta Motia grade 1 - Farooqui, Fozia Ahsan (Karachi : Oxford university press, 2023)
"Oxford Urdu Ka Guldasta Motia (Grade 1)" is a collection of simple and engaging Urdu stories and poems for young children. The book introduces basic Urdu vocabulary and language skills through fun and colorful illustrations. It features a variety of short stories and rhymes that help children develop a love for reading and an understanding of important moral lessons. Designed for grade 1 students, it encourages early literacy while nurturing an appreciation for the Urdu language
Keywords: Urdu : Textbook